MAKING THE BEST OUT OF THE WORST: UTILIZING INDONESIA’S EXISTING LAWS TO PROTECT ASYLUM SEEKERS IN TRANSIT - Rahmani, Tanita Dhiyaan (UI Scholars Hub, 2018)
Being a party in the 1951 Convention on the Status Relating to Refugees and its 1967 Protocol is not an exclusive solution to legal protection of asylum seekers and refugees in Indonesia. Although the Government of Indonesia has not ratified both instruments, it has acknowledge the protection of asylum seekers and refugees under the People Consultative Assembly (MPR) Decree Number XVII Year 1998 and Law Number 37 year 1999 regarding Foreign Relations. A 2016 United Nations High Commissioner for Refugees reported that Indonesia has become a transit destination for more than 13,000 asylum seekers and refugees, including nearly 1,000 Rohing- ya asylum seekers. Asylum seekers suffers the most in Indonesia’s legal imbroglio. Despite the existing laws, the government of Indonesia has been identifying asylum seekers as illegal migrants under Immigration Law and kept them inside Immigra- tion Detention Centres (IDCs), with common reports on ill-treatment and rampant violence. As a transit country, Indonesia carries the moral and legal responsibility to protect refugees during their transit with the ultimate purpose to prepare them to be resettled in countries that have signed the 1951 Convention. During this commonly lengthy and uncertain period or transit where the United Nations High Commissioner for Refugees or International Organization of Migrants will issue their refugees ap- plication result, protection should not be absent. Instead of suggesting Indonesia to ratify the 1951 Convention on the Status Relating to Refugees and its 1967 Protocol, this paper argues that Indonesian existing laws and regulations have provides it with national and international obligations to protect asylum seekers in transit, including to refrain from refoulement action. Thus, rendering the claim of an absence legal basis an irrelevant excuse.